Was the Possibility of Conversion to Judaism Denied in the Second Temple Period? - Orian, Matan (Jewish Quarterly Review)
A scholarly view that relies heavily on 4Q174 and Jubilees maintains that during the Second Temple period, one Jewish school of thought denied non-Jews the option to become Jews. Other Qumran scrolls, however, acknowledge the existence of proselytes, while the Temple Scroll accords them Temple access. This essay suggests that rather than articulating contrasting views, these sources can be read as presenting a coherent view on the generations-long process of becoming Jews.To be specific, 4Q174, the Temple Scroll, and Jubilees negate any Jewishness of a male convert to Judaism, owing to the deviation from the command of circumcision on the eighth day, in Genesis 17.14. However, following Ezekiel 47.22, these texts do not deny Jewishness to that convert's male descendants who are circumcised on the eighth day. Thereafter, following Deuteronomy 23.2–9, the Temple Scroll and 4Q174 admit these descendants into the Temple. At first, according to the Temple Scroll, they are considered only partially Jews, but after several generations they become "full Jews."References in Josephus and rabbinic literature to Herod and Agrippa I, the descendants of an Idumean convert to Judaism, suggest that this was not a sectarian view alone. Furthermore, Herod may have played an active role in mitigating the pertinent law to be able to reign as king of Judea, in accordance with Deut 17.15.